From Violence to Virality: A Quantitative Analysis of Online Conversations Following the 2024 Terrorist Attacks in Germany - Calabresi, Livio; Zizza, Michele (MIMESIS, 2025)
Terrorist attacks are no longer isolated acts of violence; they are also events that reverberate within an interconnected platform ecosystem, where public discourse is shaped by online narratives and social media engagement. This study provides a quantitative analysis of online conversations following three major terrorist attacks that occurred in Germany in 2024: the Mannheim stabbing (May 31st), the Solingen attack (August 23rd), and the Magdeburg Christmas market incident (December 20th). The research examines engagement levels, keyword frequencies, hashtag usage, and platform-specific trends, offering valuable insights into terrorism-related narratives evolve in digital spaces. Through automated sentiment analysis and keyword tracking, this research highlights how public discourse on terrorism intertwines with broader ideological debates on immigration, security policies, and religious identity. These findings primarily contribute to media studies, specifically focusing on mediatization of terrorism and security crisis, offering insights into how digital ecosystems mediate public reactions to violence. The results underscore the need for responsible media reporting and nuanced policy responses to mitigate the spread of unregulated narratives and stigmatization of minority communities, fostering a more informed public discourse on security and radicalization.